2020
DOI: 10.1186/s43043-020-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive technology and the risk of gestational diabetes mellitus: a systematic review and meta-analysis

Abstract: Background: The use of assisted reproductive technology (ART) is increasing worldwide, and observational studies have indicated that women who conceived by ART have an increased risk of pregnancy complications including gestational diabetes mellitus (GDM). We aimed to determine the risk of GDM among women who conceived with ART by systematic review and meta-analysis. Main text: A systematic literature search was conducted in ISI Web of Knowledge, MEDLINE, Scopus, and Embase through May 2017 for English-languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 91 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…Similarly, as other studies [ 258 , 259 , 260 ] we observed that infertility and an infertility treatment may be associated with an increased risk of GDM onset. The incidence of infertility and infertility treatment was significantly higher in groups of mothers with a GDM complicated course of gestation when compared to the group of mothers with normal pregnancies ( Table 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, as other studies [ 258 , 259 , 260 ] we observed that infertility and an infertility treatment may be associated with an increased risk of GDM onset. The incidence of infertility and infertility treatment was significantly higher in groups of mothers with a GDM complicated course of gestation when compared to the group of mothers with normal pregnancies ( Table 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…As it is argued to promote healthy implantation and placentation, IVI might reduce the risk of placenta mediated pregnancy complications (e.g. pre‐eclampsia) which are more common in women undergoing ART 32 . Planned long‐term follow‐up of randomized cohort is essential to precisely evaluate such protective effects and aid more robust evidence synthesis on ART add‐ons.…”
Section: Discussionmentioning
confidence: 99%
“…pre-eclampsia) which are more common in women undergoing ART. 32 Planned longterm follow-up of randomized cohort is essential to precisely evaluate such protective effects and aid more robust evidence synthesis on ART add-ons. Despite our meta-analysis results suggesting IVI intralipid increased both clinical pregnancy rate and live birth, the small number of studies makes it challenging to draw firm conclusions as to the benefit of intralipid.…”
Section: Implications For Future Practicementioning
confidence: 99%
“…Diabetic parents pose a higher risk of type-1 diabetes to their children independent of the conception method. This is plausible as a systematic review has reported a 51% significant increase in diabetes mellitus among parents who conceived by ART compared with those who conceived spontaneously [ 42 ].…”
Section: Discussionmentioning
confidence: 99%